Exploring the Integration of TPACK in Post-Pandemic Biology Education: A Study of Teachers in Magelang City - Muhammad Khoirul Antony; Sendy Putra Pradana; Ahmad Naharuddin Ramadhan; Susi Dewiyeti; Iful Amri (BIOPENDIX, 2025)
This research aims to explore deeper into the perspectives of biology teachers in the Magelang city regarding the crucial of TPACK in post-pandemic learning to support the professional development of teachers and create more relevant and high-quality learning. The method applied in this research is qualitative interviews. The respondents in this study consisted of 9 biology teachers in Magelang city. The TPACK framework is essential for effectively integrating technology, pedagogy, and content, though challenges remain in selecting appropriate tools and ensuring student engagement. The COVID-19 pandemic accelerated technology adoption, and teachers emphasized the need for continuous training and support to improve technology integration. Overall, with adequate resources and training, technology can greatly transform biology learning.